Challenges and Opportunities for Implementing Library Automation and Visitor Experience in the Era of the Industrial Revolution 4.0 - Dodi Nofri Yoliadi; Serjuasa Rumba; Thoriq Buchory (IAIN Batusangkar, 2023)
The library is one of the institutions that provides services, both traditional (borrowing and returning) and modern (digital). Therefore, the library is important to be able to provide the best service for users. In relation to the digital ecosystem and the era of the industrial revolution 4.0, where the library user model is a virtual community, libraries need to provide innovative services, one of which is the application of the concept of library automation and visitor experience. This paper aims to explain the concept of library automation and visitor experience and its application in libraries during the fourth industrial revolution. The method used to explain these objectives is a descriptive method with observational data collection methods and literature reviews using various scientific reference sources, both printed books and electronic books, articles, and news. The results of this paper show that the application of the concept of library automation and visitor experience in the library can be done in five ways. The first is understanding real customers from digital users; the second is rearranging the strategy from a traditional base to an experiential basis; the third is the latest management and service models; the fourth is individuals and work culture; and the fifth is being aware of human and ecological issues.